2001
DOI: 10.1104/pp.125.2.1074
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Responses to Aphid Feeding in Arabidopsis in Relation to Plant Defense Pathways

Abstract: Little is known about molecular responses in plants to phloem feeding by insects. The induction of genes associated with wound and pathogen response pathways was investigated following green peach aphid (Myzus persicae) feeding on Arabidopsis. Aphid feeding on rosette leaves induced transcription of two genes associated with salicylic acid (SA)dependent responses to pathogens (PR-1 and BGL2) 10-and 23-fold, respectively. Induction of PR-1 and BGL2 mRNA was reduced in npr1 mutant plants, which are deficient in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
476
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 502 publications
(519 citation statements)
references
References 49 publications
27
476
1
2
Order By: Relevance
“…Higher chitinase and glucanase activities did not occur in greenbug-resistant sorghum (Krishnaveni et al, 1999). Likewise, induction of SA-dependent responses did not confer resistance to green peach aphid in Arabidopsis (Moran and Thompson, 2001). In contrast, control of insect pests including phloemfeeders by JA-regulated genes such as protease inhibitors has been established (Rahbe and Febvay, 1993;Tran et al, 1997).…”
Section: Are Plants Misled By Aphids?mentioning
confidence: 97%
See 2 more Smart Citations
“…Higher chitinase and glucanase activities did not occur in greenbug-resistant sorghum (Krishnaveni et al, 1999). Likewise, induction of SA-dependent responses did not confer resistance to green peach aphid in Arabidopsis (Moran and Thompson, 2001). In contrast, control of insect pests including phloemfeeders by JA-regulated genes such as protease inhibitors has been established (Rahbe and Febvay, 1993;Tran et al, 1997).…”
Section: Are Plants Misled By Aphids?mentioning
confidence: 97%
“…A common feature among reported studies on plant-aphid interactions is that plants activate genes known to mount defenses against bacterial and fungal pathogens (Fidantsef et al, 1999;Moran and Thompson, 2001;Moran et al, 2002). Such a response is generally not stimulated by chewing insects (Reymond et al, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, expression of genes involved in sugar transport and metabolism were altered in GPA infested Arabidopsis (Moran and Thompson, 2001;Moran et al, 2002;Pegadaraju, 2005). The concentration of sucrose and starch increased in GPA-infested leaves of Arabi-dopsis (Singh et al, 2011).…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
“…This imbalance is starting to change, however, as molecular tools are applied to the study of induced responses to phloem feeding and to mechanisms of genetic resistance (for review, see Walling, 2000;Kessler and Baldwin, 2002;Moran et al, 2002). Studies with Arabidopsis (Arabidopsis thaliana) and cultivated species have identified changes in gene expression when plants are challenged with phloem feeders (Walling, 2000;Moran and Thompson, 2001;Moran et al, 2002;de Ilarduya et al, 2003;Zhu-Salzman et al, 2004). Considering the intimate and enduring contact of insect stylets with the host tissue, it is not surprising that these and other studies have found remarkable similarities between plant responses to phloem feeders and pathogens.…”
mentioning
confidence: 99%